STUDI FENOMENOLOGI: DUKUNGAN PADA IBU DALAM PERAWATAN BAYI PREMATUR DI RUANG RAWAT INTENSIF NEONATUS - Yugistyowati, Anafrin (Media Ilmu Kesehatan, 2018)
Background: The premature birth of infants is a process that leads to physical unpreparedness, sources of stress, and traumatize effects for the parents. Mostly mothers showed unpleasant memories that interfered the parents’ ability to take care of their premature baby. Objective: This study aimed  to obtain in-depth understanding of mother’s support in neonatal  intensive care ward. Methods: This is a qualitative research using phenomenology approach involving eight participants. Data were collected through in-depth interview using data recording, interview protocol, and field note. Colaizzi method was used to analyse data. Results: Two research themes were gained from data analysis, the source and the type of support for mother with premature infants’ care. Conclusion: This study recommends for nurses to assist parents by discussing any problems and to facilitate bonding mother and baby through implementation continuum of discharge planning.   Keywords: Care for Premature Infants, Neonatal Intensive Care Ward, Supporting Mothers